Canopy temperature depression for droughtand heat stress tolerance in wheat breeding - S. B. Lepekhov (Вавиловский журнал генетики и селекции)
An infrared thermometer was first used to assess drought and heat tolerance in plant breeding more than 40 years ago. Soon afterward, this method became widely used throughout the world. However, Russia has not yet applied the described method for evaluating stress tolerance. This paper presents an overview of using infrared thermometry in plant breeding. Taking wheat as an example, it shows major advantages and disadvantages of canopy temperature depression (CTD) values measured by the infrared thermometer. The paper also demonstrates that genotypes with higher CTD values, and therefore with a lower canopy temperature, use more available soil moisture under drought stress to cool the canopy by transpiration. It refers to CTD as an integrative trait that reflects an overall plant water status. Its coefficient of variation lies in the interval of 10 to 43 %. A large number of publications illustrate a close relation between CTD values and yield and indicate a high heritability of the former. Meanwhile, the same works show that yield has a higher heritability. Moreover, some researchers doubt that CTD should be used in applied wheat breeding as there are many factors that influence it. CTD has a high correlation with other traits that reflect plant water status or their adaptation to drought or heat stress. Quantitative trait loci (QTLs) associated with CTD are localized in all chromosomes, except for 3D. These QTLs often explain a small part of phenotypic variance (10–20 %, more likely less than 10 %), which complicates the pyramiding of canopy temperature genes through marker-assisted selection. The paper concludes that the evaluation of CTD appears to be a reliable, relatively simple, labor-saving, objective, and non-invasive method that sets it apart from other methods as well as shows the best results under terminal drought and heat stress conditions.